DOP43 Impact of Inflammatory Bowel Diseases on the phenotype and severity of psoriasis and spondyloarthropathies. (27th May 2021) - Attauabi, M; Damsgaard Wewer, M; Bendtsen, F; Seidelin, J B; Burisch, J
Abstract: Background: It is unclear whether inflammatory bowel diseases (IBD) affect the phenotype and severity of co-occurring axial spondyloarthropathies (axSpA) and psoriasis. Therefore, we aimed to investigate the characteristics of axSpA and psoriasis in relation to co-occurring IBD. Methods: The systematic review and meta-analysis were conducted according to Cochrane's recommendations. PubMed and EMBASE were searched from database inception till January 2020 for studies reporting disease phenotype and severity of axSpA and psoriasis in association with co-occurrence of IBD. Meta-analyses were performed using a random-effects model. Quality of the studies was assessed by the Newcastle-Ottawa Scale (NOS). Results: The electronic search yielded 12, 220 studies which were narrowed down to 152 after screening based on study titles and abstracts. Of these, a full-text review identified 20 eligible studies, including twelve and eight studies describing characteristics of axSpA and psoriasis, respectively, in relation to IBD. AxSpA was identified among a total of 321 and 8, 660 patients with and without a co-occurring IBD, respectively, and the studies' mean NOS score was 6.8, including seven and five studies of moderate and high quality, respectively. The meta-analysis demonstrated that presence of co-occurring IBD was associated with an increased risk of dactylitis (risk ratio (RR)=2.06 (95%CI 1.24–3.42), I 2 =0%), but not enthesitis (RR=0.93 (95%CI 0.48–1.81), I 2 =86%). Furthermore, IBD was associated with a significantly lower Bath Ankylosing Spondylitis Radiology Index (mean difference (meandiff) -2.28 (95%CI -3.26-(-1.30)), p<0.01, I 2 =0%), better Schober's test results (meandiff 0.80 (95%CI 0.64–1.49), p<0.01, I 2 =0%), and a lower finger to floor distance (meandiff -6.36 (95%CI -10.36-(-2.36)), p<0.01, I 2 =0%). The phenotype of psoriasis was assessed among 680 and 222, 279 patients with and without a co-occurring IBD. The mean NOS score was 7.4, including two studies of moderate methodological quality, while the remaining six studies were of high quality. The presence of IBD was associated with a significantly less frequent presentation of psoriasis in the nails (RR=0.14 (95%CI 0.05–0.42), I 2 =0%) but not psoriatic arthritis (RR=0.94 (95%CI 0.27–3.31), I 2 =75%). Finally, the presence of IBD was associated with a milder phenotype of psoriasis (RR=1.41 (95%CI 1.02–1.96), p=0.04, I 2 =70%). Conclusion: This is the first systematic review with meta-analysis investigating the impact of IBD on the disease phenotype and severity of psoriasis and axSpA. Our data suggest that IBD modifies psoriasis and axSpA to be milder and emphasizes the importance of a multidisciplinary approach to patients with psoriasis or axSpA and co-occurring IBD.